Unfolding, Embracing, and Reflecting on the Narrative Within Nutrition and Dietetics. Issue 2 (April 2015) - Habash, Diane L.
<x xml:space="preserve">Abstract</x> Dietitians are dedicated to the task of helping people make diet and lifestyle changes that meet health goals. Using interpersonal skills for listening and counseling, dietitians translate nutritional sciences and medical nutrition therapy to healthy foods, beverages, and behaviors for and with their clients. Recently, in medicine, increasing emphasis has been placed on embracing the client's narrative (story), to establish an impactful "therapeutic alliance with the client." This article uses story to illustrate the domain of narrative medicine applied to nutrition, dietetics, and lifestyle counseling to examine both process and potential impact on the client from a dietitian's perspective.